2016
DOI: 10.3390/ma9090749
|View full text |Cite
|
Sign up to set email alerts
|

Passivation Characteristics of Alloy Corrosion-Resistant Steel Cr10Mo1 in Simulating Concrete Pore Solutions: Combination Effects of pH and Chloride

Abstract: The electrochemical behaviour for passivation of new alloy corrosion-resistant steel Cr10Mo1 immersed in alkaline solutions with different pH values (13.3, 12.0, 10.5, and 9.0) and chloride contents (0.2 M and 1.0 M), was investigated by various electrochemical techniques: linear polarization resistance, electrochemical impedance spectroscopy and capacitance measurements. The chemical composition and structure of passive films were determined by XPS. The morphological features and surface composition of the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Previous studies have shown that the compositions of passive films for stainless steel in alkaline environments are mainly chromium and iron oxides . Therefore, the high‐resolution XPS depth spectra of Cr 2p 3/2 and Fe 2p are particularly shown in this study (Figures and ).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Previous studies have shown that the compositions of passive films for stainless steel in alkaline environments are mainly chromium and iron oxides . Therefore, the high‐resolution XPS depth spectra of Cr 2p 3/2 and Fe 2p are particularly shown in this study (Figures and ).…”
Section: Resultsmentioning
confidence: 72%
“…Therefore, the high‐resolution XPS depth spectra of Cr 2p 3/2 and Fe 2p are particularly shown in this study (Figures and ). On the basis of the binding energies reported in the literature, Cr 2p 3/2 spectra can be classified into three contributions: metallic Cr (Cr 0 574.1 eV), Cr III oxide (Cr 2 O 3 576.3 eV) and hydroxide form (CrOOH/Cr(OH) 3 577.3 eV), whereas the Fe 2p 3/2 signal is separated into four peaks: Fe 0 (706.8 eV), FeO (709.5 eV), Fe 2 O 3 (710.7 eV), and FeOOH (711.8 eV).…”
Section: Resultsmentioning
confidence: 99%
“…This leaching mode is likely why it destabilized at pH 11, and subsequently precipitated as hydroxides. At higher pH values it is well known from corrosion studies that passivatingxide/hydroxide layers (MOOH, M(OH) 2 ) are formed . S leaching is likely to occur via H 2 O (S+2 H 2 O→S 2− +2 OH − ) and is reported to be first order in H + (effectively present as H 2 O at high pH) .…”
Section: Resultsmentioning
confidence: 99%
“…The new type of reinforced bar is alloyed with about wt.10% Cr and wt.1% Mo, consisting of granular bainite with ferrite between the grains, and was developed by Southeast University [26]. Laboratory tests showed that the Cr10Mo1 reinforced bar has a critical chloride threshold level five times higher than that of carbon steel [27]. This is the first time that this new type of alloy has been used in a huge construction project in China, and the price is about 8000 RMB per ton (equal to 1140 USD per ton, approximately).…”
Section: Introductionmentioning
confidence: 99%